ANALYSIS OF INTERNAL FACTORS AFFECTING THE PROFITABILITY OF TEXTILE AND LEATHER INDEX COMPANIES ON THE ISTANBUL STOCK EXCHANGE (BIST) (Third Sector Social Economic Review, 2022)
AbstractThe most crucial tool for maximizing market value is profitability. Together with the linked industries, the textile and leather industries, which play a significant role in the Turkish economy, are crucial for the national economy. The study's objective is to examine the internal firm-specific characteristics that have an impact on the profitability of the businesses included in the Borsa Istanbul (BIST) Textile and Leather Index. For this reason, 20 companies in the relevant index provided access to financial statements for 17 companies for the years 2013 through 2021. In the study, where the return on assets ratio was chosen as the dependent variable, eleven financial ratios—which display a company's capacity for repaying short-term debts, capital structure, effectiveness, and scale of operations—were chosen as the independent variable. According to the analysis done with panel regression, the operating profit ratio, asset size, net working capital ratio, asset turnover, inventory turnover, and receivables turnover all have a positive impact on the firm's profitability, while the financial leverage ratio, debt equity ratio, and current ratio have a negative impact.
Keywords: Profitability; Panel Regression Analysis; BIST Textile and Leather Index; ROA; Determinants of Profitability